Gene therapy: a possible future standard for HIV care. Issue 7 (July 2015) - Abou-El-Enein, Mohamed; Bauer, Gerhard; Reinke, Petra
<x xml:space="preserve">Abstract</x> Despite undeniable accomplishments in developing cell and gene therapeutic strategies to combat HIV infection, key social, economic, and policy-related challenges still need to be overcome for any future commercialization efforts of these novel therapies to be successful. Here, we address these challenges and structure a framework for eradicating HIV/AIDS using gene therapy.